Automatic geotagging using GPS EXIF metadata of smartphone digital photos in tree planting location mapping. Issue 4 (June 2021) - Prasetiyo, B; Alamsyah; Muslim, M A; Subhan; Baroroh, N
Abstract: Tree planting is one of the programs that are currently being promoted. The location of tree planting is important to be monitored in the future. Tree planting activities carried out on the UNNES campus always carry out online documentation and reporting. However, the problem is the difficulty in obtaining the coordinates of the location of the plants because what is currently done is clicking on maps manually. In this research, we designed automated geotagging tree planting photos. Digital photos from smartphones are read, then extracted EXIF information to get GPS coordinates. Then the coordinates are obtained automatically, then stored in the database. The coordinates can be reversed to display on maps. In our experiment, we study in two cases. Case 1 the original photo near the building, Case 2 the photo near the forest. We can show that the result of mapping represents the actual state of the photo. So, the use of GPS information on photo smartphones can be an alternative solution in terms of documenting planting photos to get an accurate location.